Pulmonary Embolism in the Post-partum Period: A Case Report - Irma Kartikasari; Syafarinah Nur Hidayah Akil (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2024)
Background: One well-known hypercoagulable state that raises the risk of venous thromboembolism is pregnancy and it is more common in cesarean delivery. Pulmonary embolisms are difficult to identify based solely on postpartum symptoms. Most of the symptoms are non-specific, therefore they are typically underdiagnosed throughout pregnancy and the postpartum period. Objective: This work presented information on the treatment of high-risk pulmonary embolism in the postpartum phase. Case presentation: This paper reported the case of a 33-year-old female, admitted to the emergency room for shortness of breath. Her personal history showed that she had just given birth to her sixth child by caesarian section a month ago and had a history of hysterectomy due to severe infection. Result: She suffered a high-risk pulmonary embolism in the post-partum period. It takes a strong index of suspicion to diagnose and treat patients in a timely manner. Conclusion: Echocardiography and Multislice Computerized Tomography are the best diagnostic methods. Venous thromboembolism prophylaxis should be taken into account, particularly in patients who have risk factors.